2002
DOI: 10.1254/jjp.89.44
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Ionotropic Glutamate Receptor Subtypes in Cultured Rat Retinal Ganglion Cells Obtained by the Magnetic Cell Sorter Method and Inhibitory Effects of 20-Hydroxyecdysone, a Neurosteroid, on the Glutamate Response

Abstract: ABSTRACT-Glutamate and neurosteroids are known to exist in retinal ganglion cells (RGC). Therefore, patch clamp studies using the whole-cell recording method were performed to determine whether or not ionotropic glutamate receptor subtypes, i.e., N-methyl-D-aspartate (NMDA), a-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) and kainate receptors, were present on RGC obtained by the magnetic cell sorter (MACS) method and cultures. In addition, the effects of 20-hydroxyecdysone (20-HE), a neurosteroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…16,55–61 The P4–P10 developmental stage is particularly advantageous for the isolation of RGCs because the apoptotic elimination of excess RGCs during development is complete, and the remaining RGCs have a functional axon in the optic nerve with arborization of presynaptic terminals within the brain. 6264 Furthermore, the relatively undifferentiated state of other neurons in the retina eases dissociation of the retina and specificity of antigen-based isolation.…”
Section: Methodsmentioning
confidence: 99%
“…16,55–61 The P4–P10 developmental stage is particularly advantageous for the isolation of RGCs because the apoptotic elimination of excess RGCs during development is complete, and the remaining RGCs have a functional axon in the optic nerve with arborization of presynaptic terminals within the brain. 6264 Furthermore, the relatively undifferentiated state of other neurons in the retina eases dissociation of the retina and specificity of antigen-based isolation.…”
Section: Methodsmentioning
confidence: 99%
“…AMPA receptors are found in AII amacrine and ganglion cells [31], [32] and metabotropic mGluR6 receptors are found in bipolar cells [33]. These two receptor types were modeled by the same equations [30].…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, it was demonstrated that NSs can modulate glutamate‐mediated transmission in several systems, including retinal ganglion cells (Wu et al . 1991; Mukai et al . 2002).…”
mentioning
confidence: 99%